NILAI INTELLECTUAL CAPITAL PADA PERUSAHAAN-PERUSAHAAN DI INDONESIA - Dyna Rachmawati; C. Erna Susilawati (Media Riset Bisnis & Manajemen, 2008)
Intellectual Capital (IC) is an intangible asset, as a hidden value, needed by company to explore the company's competitive advantages. This study tried to identify IC as one of company's resources to generate earnings. We propose 5 valuation models to identify IC role as one of firm value from price and earnings.There are 3 hypotheses that have been proposed in this study. The first hypothesis is proved by valuation model 1-4. The result shows that IC has influenced significantly to share price. The second and third hypothesis has failed to accept. We use valuation model 5 to prove these hypotheses. Those are implied that IC has not been used optimally to generate earnings.This study concludes that companies in Indonesia have not yet have the capabilities to innovate and creativity in order to generate eamings. Companies in Indonesia are more tangible insentive rather than intangible insentive.Keywords: Intellectual capital, Share price, Earnings